Neuropedagogical features of teaching primary school students to read and understand text - Sotivoldiyeva Sarvinoz Qahramon qizi (Zien Journals, 2023)
This article describes the neuropedagogical features of teaching elementary school students to read and understand the text.
Keywords: Neuropedagogy; text; interpretive reading